2018
DOI: 10.3390/ijms20010025
|View full text |Cite
|
Sign up to set email alerts
|

Role of Green Macroalgae Enteromorpha Prolifera Polyphenols in the Modulation of Gene Expression and Intestinal Microflora Profiles in Type 2 Diabetic Mice

Abstract: Effects of green macroalgae 55% ethanolic extract Enteromorpha prolifera through an ultrafiltration membrane of 3 kDa (EPE3k) on antidiabetic activity, gut microbiota, and regulation mechanism were investigated in high-fat/high-sucrose diet and streptozocin-induced diabetic mice. The structural characterizations of its major compounds in EPE3k were determined by ultra-performance liquid chromatography-quadrupole/time of flight mass spectrometry. Furthermore, the intestinal microflora modulation in diabetic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…As a traditional target of inulin [18], Faecalibacterium is well known for conferring health benefits and has been shown to decrease lipid accumulation, improve insulin sensitivity, and increase fatty acid oxidation and adiponectin signaling [41,42]. Moreover, we found that Turicibacter decreased in three gut sites for inulin-fed pigs, an effect which has previously been reported to be correlated with steroid and lipid metabolism [43] and is negatively correlated with protein and energy digestibility in low-fiber feeding growing-finishing pigs [44]. In addition, Turicibacter is involved in inhibition of phosphatidylinositol 3-kinase, and triggering c-Jun N-terminal kinase in a rat type 2 diabetic model leads to increased body weight and fasting glucose level [45].…”
Section: Discussionsupporting
confidence: 63%
“…As a traditional target of inulin [18], Faecalibacterium is well known for conferring health benefits and has been shown to decrease lipid accumulation, improve insulin sensitivity, and increase fatty acid oxidation and adiponectin signaling [41,42]. Moreover, we found that Turicibacter decreased in three gut sites for inulin-fed pigs, an effect which has previously been reported to be correlated with steroid and lipid metabolism [43] and is negatively correlated with protein and energy digestibility in low-fiber feeding growing-finishing pigs [44]. In addition, Turicibacter is involved in inhibition of phosphatidylinositol 3-kinase, and triggering c-Jun N-terminal kinase in a rat type 2 diabetic model leads to increased body weight and fasting glucose level [45].…”
Section: Discussionsupporting
confidence: 63%
“…The lower MW fractions probably contained phenolic compounds as well (as suggested by their FT-IR spectra), but the higher concentration of small organic and inorganic contaminants might explain their lower activities. Other reports of similar studies, illustrating the inclusion of UF in the fractionation of phlorotannins [80,148] or other phenolic compounds [120], can be found.…”
Section: Other Primary Separation Methodsmentioning
confidence: 77%
“…Other separations of complex extracts have been performed prior to preparative or analytical chromatography by means of ultrafiltration (UF) [80,120,140], molecular-weight cut-off dialysis (MWCOD) [28,78,166], a combination of these two [148], and capillary electrophoresis (CE) [167]. UF and MWCOD are techniques that segregate compounds by their molecular weight (MW) with less instrumental requirements, time, expertise, or investment than the alternatives.…”
Section: Other Primary Separation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various polyphenols have also been shown to modulate the expression of insulin receptors substrate 1 (IRS-1), serine/threonine protein kinase 1 (Akt 1) and phosphoenolpyruvate carboxykinase (PEPCK) in human hepatoma cells (HEPG2) [11]. The positive effects of polyphenols on these pathways are correlated with improved β-cell function, insulin sensitivity, reduced inflammation and lipotoxicity and reduced hepatic glucose output, collectively accounting for normal glucose homeostatic function [12]. This review discusses the impact of polyphenols on regulating gene expressions in major metabolic pathways associated with the development of T2DM.…”
Section: Introductionmentioning
confidence: 99%